Dynamic metabolic change is indicative of inflammation-induced transformation of hepatic cells. (September 2015) - Peng, Bo; Liu, Fan; Han, Rong; Luo, George; Cathopoulis, Terry; Lu, Kun; Li, Xiao; Yang, Ling; Liu, Guo-Yan; Cai, Jian-Chun; Shi, Song-Lin
Abstract: The observation that prolonged inflammation plays a causative role in cancer development has been well documented. However, an incremental process that leads from healthy to malignant phenotypes has not yet been described. Experimentally induced hepatocellular carcinoma is considered one of the representative laboratory models for studying this process. Hepatic exposure to viral infection or toxic reagents leads to chronic inflammation and gradual transformation into hepatocellular carcinoma. Here we present metabolomic profiles of hepatic cells at different stages during inflammation-induced cellular transformation by N-nitrosodiethylamine. Using gas chromatography–mass spectrometry, we quantitatively assessed the changes in cellular metabolites during the transformation process in hepatitis and liver cirrhosis. Further pathway analysis of the differentially expressed metabolites showed that carbohydrate metabolism and lipid metabolism were greatly altered in hepatitis and liver cirrhosis, respectively. Additionally, the enhanced inflammation in cirrhosis was associated with a shift from carbohydrate metabolism to lipid and amino acid metabolism. Among the differentially expressed metabolites found in diseased mouse livers, d -glucose and d -mannitol showed the most significant changes, highlighting them as potential early-diagnostic biomarkers of hepatocellular carcinoma development. Taken together, these investigations into the dynamic metabolic changes that occur during the precancerous stages of hepatocellular carcinoma add to and refine understanding of how chronic inflammation ultimately leads to cancer. Furthermore, the findings set the stage for identifying metabolites that may serve as early-diagnostic indicators of these unfolding events.